Shaping ability of ProTaper Ultimate and BlueShaper in mandibular molars: a micro-CT evaluation - Greco, Katia; Iacono, Francesco; Montagna, Francesco; Esposito Corcione, Carola; Paolone, Gaetano; Gherlone, Enrico; Cantatore, Giuseppe (Frontiers in Materials, 2024)
Aim to evaluate the shaping characteristics of ProTaper Ultimate (Dentsply Sirona) and BlueShaper (Zarc4Endo) using micro-computed tomographic imaging technology (micro-CT). Methods Thirty mesial and distal canals of extracted second mandibular molars with similar anatomy were selected, scanned pre- and postoperatively by using micro-CT scanning (SkyScan 1172, Bruker- microCT) with a voxel size of 11μm and shaped with two different procedures: ProTaper Ultimate (Group 1: n=15) and BlueShaper (Group 2: n=15) were used following the manufacturer’s recommendations up to final 30 apical size. Irrigation was ensured in all groups with 5.25% NaOCl and 10% EDTA during instrumentation. Canal transportation, volume of removed dentin and area of untreated surface were matched with preoperative values with Bruker CT Analyser (Bruker- microCT). Data were statistically analyzed using Student’s t test. Results No significant differences were observed between Group 1 and Group 2 in terms of canal transportation, volume of removed dentin and untreated surfaces. A significant difference (p<0.05) was found regarding untreated surface between mesial and distal canals in both groups. Conclusions Shaping procedures with both ProTaper Ultimate and BlueShaper demonstrated similar volume of canal enlargement and similar canal transportation without evidence of significant preparation errors. Nevertheless, a high amount of untreated surface was reported for both systems, particularly in distal canals.